2022
DOI: 10.1186/s13047-022-00555-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 pandemic on foot care services in Ontario, Canada

Abstract: Background The COVID-19 pandemic has directly affected the delivery of health care services in Canada, including foot care. The goal of this descriptive study was to understand the impact of the early COVID-19 pandemic (March 2020 to April 2021) on chiropodists’ and podiatrists’ clinical practices and foot care service delivery in Ontario, Canada. Methods A web-survey was completed by participating chiropodists and podiatrists registered with the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The COVID-19 pandemic was additionally associated with a reduction in outpatient foot clinic patient numbers, a rise in urgent foot health issues, and had a negative influence on the mental and emotional wellbeing of medical professionals. 23 While the majority of health services switched largely to virtual clinics during the pandemic, we continued to see patients with DFU face-to-face in our service, although we did have to reduce the number of patients seen per clinic. This usual face-to-face clinic experience may explain why most patients reported that they felt the pandemic had no impact on their diabetic foot care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic was additionally associated with a reduction in outpatient foot clinic patient numbers, a rise in urgent foot health issues, and had a negative influence on the mental and emotional wellbeing of medical professionals. 23 While the majority of health services switched largely to virtual clinics during the pandemic, we continued to see patients with DFU face-to-face in our service, although we did have to reduce the number of patients seen per clinic. This usual face-to-face clinic experience may explain why most patients reported that they felt the pandemic had no impact on their diabetic foot care.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID‐19 pandemic amputation rates increased considerably, with associated impacts – medically, psychosocially and economically; 22 an increase to which this delay in seeking medical advice potentially contributed. The COVID‐19 pandemic was additionally associated with a reduction in outpatient foot clinic patient numbers, a rise in urgent foot health issues, and had a negative influence on the mental and emotional wellbeing of medical professionals 23 . While the majority of health services switched largely to virtual clinics during the pandemic, we continued to see patients with DFU face‐to‐face in our service, although we did have to reduce the number of patients seen per clinic.…”
Section: Discussionmentioning
confidence: 99%